Lack of association between the Trp719Arg polymorphism in kinesin-like protein-6 and cardiovascular risk and efficacy of atorvastatin among subjects with diabetes on dialysis: The 4D study - Hoffmann, Michael Marcus; März, Winfried; Genser, Bernd; Drechsler, Christiane; Wanner, Christoph (Atherosclerosis, 2011)
Aims - We investigated whether KIF6 Trp719Arg genotypes affect cardiovascular outcomes and efficacy of statin therapy in patients with type 2 diabetes mellitus undergoing hemodialysis. - Methods and results - We conducted a post hoc analysis of the 4D-study, a randomized trial including 1255 patients. Patients were randomly assigned to double-blind treatment with either 20mg of atorvastatin (n=619) or placebo (n=636) once daily and followed for 4 years (median). DNA was available for 1232 patients and we assessed KIF6 Trp719Arg genotypes by PCR and subsequent restriction digest. Carriers of the Arg719 allele showed no increased prevalence of cardiovascular disease. The incidence of cardiac death, MI, and stroke did not differ across KIF6 genotypes, irrespective of whether the patients were treated with atorvastatin or not. - Conclusion - In patients with type 2 diabetes mellitus on hemodialysis, KIF6 Trp719Arg genotypes were not associated with adverse cardiovascular outcomes during follow-up or with the efficacy of atorvastatin therapy.